Penerapan Edukasi dengan Media QR Code Siceting (Sigap Cegah Stunting) Dalam Meningkatkan Pengetahuan Ibu Dengan Anak Usia 6-59 Bulan di Wilayah Kerja Puskesmas Tilongkabila - Syahrir, Akifa; Agung Salim (Jurnal Stunting Pesisir dan Aplikasinya, 2024)
Stunting is a condition in children caused by chronic malnutrition during growth, typically beginning in the womb or during the first 1,000 days of life. One relevant digital medium that is easy to apply and significantly benefits the educational process is the QR Code based on digital devices. Objective: To determine the effect of the QR Code SICETING (Proactive Stunting Prevention) on the knowledge of mothers with children aged 6- 59 months in the work area of the Tilongkabila Health Center. Methods: This case study is a descriptive case study conducted using quantitative research methods. This study involved mothers with children aged 6-59 months as criteria, and observation of five respondents was used to assess the difference in knowledge about stunting before and after using the QR Code SICETING. The instrument used to measure knowledge was a questionnaire consisting of 20 items with 2 alternative answers (True/False). Results: The case study results indicated that with the intervention of education using the QR Code SICETING media, there was a significant increase in knowledge about stunting among mothers. All five subjects experienced an increase in knowledge about stunting with a score improvement of 30-35%. Conclusion: Based on the case study results, it can be concluded that the QR Code SICETING (Proactive Stunting Prevention) media can increase knowledge about stunting among mothers with children aged 6-59 months in the work area of the Tilongkabila Health Center.